1995
DOI: 10.1007/bf00385647
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk assessment for health care workers occupationally exposed to cyclophosphamide

Abstract: In the present study a cancer risk assessment of occupational exposure to cyclophosphamide (CP), a genotoxic carcinogenic antineoplastic agent, was carried out following two approaches based on (1) data from an animal study and (2) data on primary and secondary tumors in CP-treated patients. Data on the urinary excretion of CP in health care workers were used to estimate the uptake of CP, which ranged from 3.6 to 18 micrograms/day. Based on data from an animal study, cancer risks were calculated for a health c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
1
6

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 24 publications
2
65
1
6
Order By: Relevance
“…Sessink et al, have reported an increased cancer risk of 1.4-10 additional cases per year per million workers exposed daily to CP, with an urinary excretion average of 180 ng/24 hr in pharmacy personnel. 19) The mean urinary concentration of CP in the samples from the 4 pharmacists in this study was as high as 165.3 ng close to the 180 ng level reported, but after the SOP was revised this decreased to 47.4 ng. The CP level of 1 pharmacist in the first test was low compared to the other 3 pharmacists.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Sessink et al, have reported an increased cancer risk of 1.4-10 additional cases per year per million workers exposed daily to CP, with an urinary excretion average of 180 ng/24 hr in pharmacy personnel. 19) The mean urinary concentration of CP in the samples from the 4 pharmacists in this study was as high as 165.3 ng close to the 180 ng level reported, but after the SOP was revised this decreased to 47.4 ng. The CP level of 1 pharmacist in the first test was low compared to the other 3 pharmacists.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, despite advancements in technologies such as electronic medical records in Japan, measures to prevent the exposure of medical professionals to antineoplastic agents are very much underdeveloped. Exposure of medical professionals to antineoplastic agents could be reduced, as in the Netherlands, 19) if urine and wipe tests were conducted at each medical institution by certain organizations or with law, that sets a target for risk levels for exposure. We strongly hope that the JSHP will notify the Ministry of Health, Labor, and Welfare of Japan (MHLW) of the risks in handling antineoplastic agents, and that this will lead to a revision of related institutions or in the NHI system to legally protect medical professionals from exposure to antineoplastic agents, and also that a system will be established for pharmaceutical companies to introduce the use of closed medical devices.…”
Section: Discussionmentioning
confidence: 99%
“…Sessink 8) and Sorsa 48) estimated the carcinogenic risk by CP absorption. Sessink 8) presumed that urinary excretion of unchanged CP was 1 5% and 180 ng of CP was continuously excreted in urine for 200 days ×40 years, and estimated that the occupational risk of developing cancer was 120 600 per million by extrapolation of incidences of tumors in rats, and proposed regular monitoring of urinary CP excretion.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, in studies of external exposures [Sessink et al,1992;Minoia et al,1998;Sabatini et al,2005;Hedmer et al,2008] and studies in internal exposures [Hirst et al,1984;Sessink et al,1992Sessink et al, , 1994Sessink et al, , 1995Ensslin et al,1994;Burgaz et al,1999;Pethran et al,2003], cyclophosphamide was frequently used as a marker of occupational exposures because of its slight volatility and human genotoxicity [Connor et al,2000], reproductive toxicity [Anderson et al,1995], carcinogenicity [IARC,1981], and ease of detection [Turci et al,2002;Barbieri et al,2006].…”
Section: Discussionmentioning
confidence: 99%